MENGEMBANGKAN STRATEGI KOMUNIKASI DAN PELATIHAN DALAM MENINGKATKAN PROMOSI INTERNAL PADA KINERJA PEGAWAI DI PEMERINTAH KOTA PALANGKA RAYA - Peridawaty, Peridawaty; Prakoso, Rian Sidiq (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
This research aims to develop effective organizational communication and training strategies in order to increase the success of internal promotions for employees within the Palangka Raya City Government. Internal promotion is one of the important instruments in fair and performance-based human resource management. However, the low effectiveness of vertical communication and limited competency development training are the main obstacles to the success of the promotion. The research was conducted through qualitative and quantitative approaches with survey, interview, and simulation training techniques. The results show that non-open communication and lack of understanding of promotional standards are the main inhibiting factors. The training designed in this activity is able to increase the understanding and readiness of employees in participating in the promotion process. The recommendations are directed at strengthening two-way internal communication and a structured and ongoing training program.